PhP.B Enhanced Adeno-Associated Virus Mediated-Expression Following Systemic Delivery or Direct Brain Administration - Pietersz, Kimberly L.; Plessis, Francois Du; Pouw, Stephan M.; Liefhebber, Jolanda M.; van Deventer, Sander J.; Martens, Gerard J. M.; Konstantinova, Pavlina S.; Blits, Bas (Frontiers in Bioengineering and Biotechnology, 2021)
Of the adeno-associated viruses (AAVs), AAV9 is known for its capability to cross the blood-brain-barrier (BBB) and can therefore be used as a non-invasive method to target the central nervous system. Furthermore, the addition of the peptide PhP.B to AAV9 increases its transduction across the BBB by 40-fold. Another neurotropic serotype, AAV5, has been shown as gene therapeutic delivery vehicle to ameliorate several neurodegenerative diseases in preclinical models, but its administration requires invasive surgery. In this study, AAV9-PhP.B and AAV5-PhP.B were designed and produced in an insect cell-based system. To AAV9, TLAPFK was added, whereas in AAV5-PhP.B (AQTLAVPFKAQAQ), with AQ-AQAQ sequences used to swap with the corresponding sequence of AAV5. The addition of PhP.B to AAV5 did not affect its capacity to cross the mouse BBB, while increased transduction of liver tissue was observed. Next, intravenous (IV) and intrastriatal (IStr) delivery of AAV9-PhP.B and AAV5 were compared. For AAV9-PhP.B, similar transduction and expression levels were achieved in the striatum and cortex, irrespective of the delivery method used. IStr AAV5 administration resulted in significantly higher amounts of vector DNA and therapeutic miRNA in the target regions striatum and cortex as compared to IV administration of AAV9-PhP.B. These results illustrate the challenge in developing a vector that can be delivered non-invasively whilst achieving a transduction level similar to that of direct administration of AAV5. Thus, for therapeutic miRNA delivery with high local expression requirements, intraparenchymal delivery of AAV5 is preferred, whereas a humanized AAV9-PhP.B may be useful when widespread brain (and peripheral) transduction is needed.